PERBANDINGAN PIPA PVC DAN PIPA GALVANIS TERHADAP EFEKTIVITAS FLOWRATE COOLANT PADA MESIN SURFACE GRINDING DI PT XYZ - Aditya Pratama Ubeng, (2020)
This study wants to find out the effectiveness comparison between the use of Galvanized pipe and PVC toward the amount of flowrate, percentage of feedrate and its implications for increasing productivity. The study was conducted at PT XYZ in the Cikarang region, West Java. This research uses a field research method which involves grinding section in the company. This research method compares the performance of Galvanized and PVC pipes related to the amount of flowrate, percentage of feedrate and its implications for increasing productivity. The results of this study prove that PVC pipes have a better performance to be able to increase the amount of flowrate that directly affects the feedrate and ultimately has implications for increased production. The increase in flowrate reached 44,6% while for the increase in feedrate by 50% and increased productivity by 25,6%.